FROM THE CLASSROOM TO THE LIVING ROOM: THE ACTIVE ROLE OF PARENTS IN SUPPORTING STUDENT ACHIEVEMENT - Julisesko Buaton; Dameria Sinaga (RADJA PUBLIKA, 2025)
Education is a process that does not only take place in the classroom, but also continues to the family room. The active role of parents has a significant influence on student achievement, both in academic and non-academic aspects. This research was conducted at Budi Mulia Mangga Besar Junior High School, Jakarta. The purpose of the study was to identify the form of parental involvement and role in supporting student achievement, and the impact of parental involvement on the development of students' academic and non-academic achievement. Participants in this study were parents, homeroom teachers, and students. The research was conducted with a non-participatory observation approach and semi-structured interviews to obtain data validity. This research was conducted in March-April 2025. The results of the study emphasized that students with good academic achievements, tend to have parents who are active in supporting their children's education both through academic assistance and emotional motivation. Students with low achievement often experience a lack of parental involvement in the learning process, which can have an impact on low motivation and learning discipline. From the results of this study, recommendations can be obtained, schools need to improve communication and education programs for parents to encourage their awareness of the importance of involvement in children's education. Collaboration between teachers and parents can be improved through more effective communication media, such as school apps or discussion groups.